Infectious Diseases Annual Volume 2022 - Garbacz, Katarzyna; Jarzembowski, Tomas; Ran, Yuping; Samie, Amidou; Saxena, Shailendra K. (Infectious Diseases, 2022)
This book is an annual collection of reviewed and relevant research chapters authored by various researchers, offering a comprehensive overview of recent studies and developments in the field of Infectious Diseases. It joins work from four areas in this field, Bacterial, Fungal, Parasitic, and Viral Infectious Diseases, each edited by an expert. The global challenges and different living circumstances for people around the globe ask for a deep understanding of various aspects and properties of infectious diseases to ensure a safer and healthier cohabitation of humans and pathogens.